Numerical Analysis of structural batteries response with the presence of uncertainty - Syahiir Kamil; Ahmad Kamal Ariffin; Abdul Hadi Azman; Mohamad Syazwan Zafwan Mohamad Suffian (Penerbit Universiti Kebangsaan Malaysia, 2023)
In order to further reduce oil dependence and world pollution, there’s growing interest in embedding batteries such as Li-Po batteries within vehicle components. The implementation of structural batteries is believed to be the next promising approach for next-generation hybrid and electric vehicles. The proposed research is devoted to the uncertainty analysis of structural battery behavior under various parameters. To help with the analysis, a dedicated algorithm based on an elimination approach to solve numerical problems with uncertain parameters is successfully developed using Visual Basic. The Constant Strain Triangle element with linear elastic behavior is used as a structural model to simplify the model. Uncertainty of the material properties and loading are modeled as Fuzzy Random Variables. In evaluating the influence of the uncertainty parameters, Interval Monte Carlo Simulation and the interval finite element method are used to compute the bounds of the structure behavior. Simulation results between the Interval Monte Carlo and Deterministic are compared to evaluate the significance of the uncertainty factor influences. It is shown that the structural batteries that can be considered safe based on deterministic parameters may be unsafe if the uncertainty parameters are considered. The proposed approach could detect the results that are not necessarily detected through deterministic means. By producing a broader result, further prevention and consideration can be made to avoid catastrophic events.